Carbon-incorporated NiO/Co3O4 concave surface microcubes derived from a MOF precursor for overall water splitting. Issue 46 (17th May 2019) - Wei, Xijun; Zhang, Yunhuai; He, Huichao; Gao, Di; Hu, Jingrui; Peng, Huarong; Peng, Li; Xiao, Shenghuan; Xiao, Peng
Abstract : Carbon-incorporated NiO/Co3 O4 concave surface microcubes (denoted as NCMC) are successfully developed from a precursor of Ni3 [Co(CN)6 ]2 for the first time. Abstract : Carbon-incorporated NiO/Co3 O4 concave surface microcubes (denoted as NCMC) are successfully developed from a precursor of Ni3 [Co(CN)6 ]2 for the first time. The NCMC exhibits excellent electrocatalytic activity for the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) in potassium hydroxide solution, affording a current density of 10 mA cm −2 at 169.5 mV for the HER and 290 mV for the OER, respectively. This communication describes a rational design of MOF-derived mixed metal oxides as electrocatalysts for overall water splitting, promoting the further development of MOF materials in the field of energy conversion.